Answer:
took the test and its 0.5
Step-by-step explanation:
.
Will you please provide more information and state a clear question
Answer:
4(2x-3)(2x + 3)
Step-by-step explanation:
Here, we want to simplify the given expression
we can have;
16x^2-36
= 4(4x^2 -9)
we can use the difference of two squares
where;
a^2 - b^2 = (a-b)(a + b)
= 4(2x-3)(2x+ 3)
Answer:
<em>Step 1: 4 x − 3 − 2 x − 10 </em>
<em>Step 2: 2 x − 13</em>
Step-by-step explanation:
Given the expression;
(4 x − 3) − 2 (x + 5)
The following steps/ procedure are to be taken when simplifying the expression.
open the parenthesis
(4 x − 3) − 2 (x + 5)
= 4x-3 -2(x)-2(5)
= 4x-3-2x-10
collect the like terms
= 4x-2x-3-10
simplify the resulting expression
= 2x-13
Hence the procedure that correctly simplifies the expression are:
Step 1: 4 x − 3 − 2 x − 10
Step 2: 2 x − 13
The dude on top of me is correct